Manual hyperinflation and the role of physical therapy in intensive care and emergency units - Rafael Vinícius Santos Cruz; Fabiana do Socorro da Silva Dias de Andrade; Pollyanna Dórea Gonzaga de Menezes; Bruno Oliveira Gonçalves; Robson da Silva Almeida; Anderson Reis Santos
Abstract Introduction: Although manual hyperinflation (MHI) is a physical therapy technique commonly used in intensive care and emergency units, there is little consensus about its use. Objective: To investigate the knowledge of physical therapists working in intensive care and emergency units about manual hyperinflation. Methods: Data were collected through self-administered questionnaires on manual hyperinflation. Data collection took place between September 2014 and January 2015, in Itabuna and Ilhéus, Bahia, Brazil. Results: The study sample was composed of 32 physical therapists who had between 4 months and 10 years working experience. All respondents affirmed that they used the technique in their professional practice. However, only 34.4% reported it to be a routine practice. 90.6% stated that the most common patient position during manual hyperinflation is "supine". Participants were almost unanimous (93.8%) in citing secretion removal and cough stimulation as perceived benefits of MHI. High peak airway pressure was identified as being a precaution to treatment with MHI by 84.4% of participants, whilst 100% of the sample agreed that an undrained pneumothorax was a contraindication to MHI. Conclusion: The most common answers to the questionnaire were: supine position during MHI; secretion removal and cough stimulation as perceived benefits; high peak airway pressure as a precaution; and an undrained pneumothorax as a contraindication.